The Mediating Effect of Employee Learning between Job Rotation and Employee Career Development: Empirical Evidence from the Banking Sector of Pakistan - Khan, Muhammad Shahid; Chongcharoen, Duangkamol; Ulhaq, Zafar (Journal of Innovation and Management, 2020)
Job Rotation is a widely accepted practice for employees learning in many organisations. The objective of this research is to use the Job Rotation concept as a career development mechanism for Management Trainee Officers (MTO’s) and assess the mediating effect of employee learning. As different organisations hiring MTO’s, this research proposes them to use Job Rotation to develop the career of newly recruited employees. The data are collected from 320 MTO’s of different commercial Banks located in Rawalpindi, Islamabad, and Peshawar. Structural Equation Model (AMOS) is used to test the model. Overall results show a positive and significant association between the constructs. Research reveals that job ration is a significant factor for employee career development and employee learning partially mediates the relationship between job rotation and career development. Research can be generalised to the banking sector and other organisations which are offering MTO programs. This research can help fresh graduates to build their career through a job rotation process, as they can learn by rotation of their position. The limitation of this research is the data collection time framework, mono method and crosses sectional approach is used, in future mixed research method can be used to explore more about job rotation concept.